Adicción a videojuegos y procrastinación académica en la unidad educativa comunitaria intercultural bilingüe EMAUS - García-Vilema, Marcia Isabel (2023)
Adolescents are especially vulnerable to the inappropriate and uncontrolled use of computer technologies. The objective of the research was to determine the relationship between the use of video games and academic procrastination in students of the second level of education. The design was observational with correlational scope. The entire population was included: 91 students from the seventh to the tenth grade of an educational unit in Ecuador. Data were collected using the Adolescent Procrastination Scale and the Video Game Related Experiences Questionnaire. 56.04% were between 10 and 13 years old and 53.85% were male. 47.25% did not show problems with video game addiction experiences, but 43.96% had potential problems. The majority had an average level of global academic procrastination (50.55%) and 46.15% scored with a high level. 74.73% had an average level of activity postponement and that same percentage showed a high level of academic self-regulation. A significant, positive, and moderate intensity correlation was established between the experience of addiction to videogames and the postponement of activity (dimension of academic procrastination).